Nonvitamin, Nonmineral Dietary Supplement Use in Individuals with Rheumatoid Arthritis. Issue 9 (17th August 2020) - Skiba, Meghan B; Hopkins, Laura L; Hopkins, Allison L; Billheimer, Dean; Funk, Janet L
ABSTRACT: Background: Over-the-counter, natural product–based (nonvitamin, nonmineral) dietary supplement (NVNM DS) use is common in adults with rheumatoid arthritis (RA), a group at risk for drug-DS interactions, due to polypharmacy, but this use is underreported to health care providers. Recent dramatic changes in US sales of specific NVNM DS suggest that the prevalence and types of NVNM DS used in RA populations may also have shifted. Objectives: A study was undertaken to identify current and past use of specific NVNM DS for RA disease treatment and to examine associations between use of NVNM DS, RA pharmaceuticals, and/or vitamin or mineral (VM) DS. Methods: We developed a survey instrument to capture current and ever use of specific NVNM DS, VM DS, and RA pharmaceuticals, with 696 subjects self-reporting an RA diagnosis recruited online or in clinic for survey participation. Analyses were limited to 611 subjects reporting RA diagnosis after age 18 y and treatment with specific RA pharmaceuticals. Results: Most participants reported DS use, with current usage prevalence 49.6% ( n = 303), 83.5% ( n = 510), or 87.6% ( n = 535) for NVNM, VM, or any DS, respectively. While not having appeared in previous RA surveys, turmeric and ginger were among the top 3 NVNM DS in current use, along with fish oil/ω-3 (n–3) PUFA. Concurrent NVNM DS use was reported by 48.2% ( n = 243) of participants currently using RA pharmaceuticals ( n = 504) and was more common in those using disease-modifying antirheumatic drugs only (no biologics). Most methotrexate users (83%) reported concurrent folate supplementation, with one-third also using turmeric, which is notable because methotrexate and turmeric have been associated with hepatotoxicity. Conclusion: Individuals with RA commonly use NVNM DS in combination with RA pharmaceuticals, including a previously undocumented but popular use of turmeric or ginger supplements with an unclear risk/benefit ratio.